Emphasized temperature dependent electrical properties study of fabricated ZnO/PVA/PANI nanocomposite films - Kanavi, Pratibha S; Meti, Sunil; Fattepur, R. H.; Patil, Veerabhadragouda B. (My University, 2022)
Polyvinyl alcohol-Polyaniline composite films with different amounts of zinc oxide (ZnO) (0.2%, 0.4%, 0.6% and 1%)were prepared by in situ polymerization followed by film casting and drying. The samples, ZnO and PPZ films, were characterized by various techniques. The presence of ZnO in PPZ films was confirmed by the X-Ray Diffractometer (XRD). The surface morphology of the ZnO and PPZ films were examined by the Field-Emission Scanning Electron Microscopy(FESEM). The formation of absorption bonds corresponding to the PPZ films were illustrated by the Fourier Transform Infrared Spectroscope (FTIR)analysis. The films were found to be stable up to 150 ◦C, which was confirmed from the Differential Scanning Calorimetry (DSC) and Thermo-Gravimetric Analyzer (TGA) technique. The absorption peaks of PPZ, around visible and UV region, was studied by the UV–Vis spectra. The electrical conductivity plots obtained from the impedance analyzer, between frequency ranges of 10 Hz to 100 kHz, show that the increase in concentration and temperature of the samples resulted in the higher conductivity of the PPZ films. For 1% ZnO concentration at 150 ◦C, the AC conductivity of PPZ1 was found to be 20.06 S/m. Such conductivity behavior samples render the applicability of the PPZ films.
Studie zdůrazněných teplotně závislých elektrických vlastností vyrobených nanokompozitních filmů ZnO/PVA/PANI
Keywords: Co-precipitation method; ZnO nanoflakes; electrical conductivity; thermal-stability; polyniline films; metoda koprecipitace; nanovločky ZnO; elektrická vodivost; tepelná stabilita; polynilinové fólie